Holistic Curriculum Integration Model for Islamic Boarding Schools and Higher Education - Sirojuddin, Akhmad; Maskuri; Ghoni, Junaidi; Hosna, Rofiatul (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2025)
This study examines the form of curriculum integration between the Amanatul Ummah Islamic Boarding School and KH Abdul Chalim University, Mojokerto, focusing on integrating Islamic moderation-based religious education and academic education that accommodates social and cultural diversity. The background of this study is the need to integrate spiritual values and social diversity into the educational curriculum, which is increasingly relevant in an increasingly pluralistic world. The primary focus of this study is to explore how these two institutions form curriculum integration as a component that teaches pluralism, tolerance, and respect for differences in the context of higher education and pesantren. This study uses a qualitative approach with a case study method, involving interviews, observations, and documentation as data collection techniques to study the two institutions' curriculum integration process. The findings of this study indicate that Pesantren Amanatul Ummah emphasises moderate religious education based on yellow books and students' social activities. At the same time, KH Abdul Chalim University integrates pluralism values in formal courses that are more global, such as Aswaja and multicultural education. The results of this study indicate that curriculum integration in both institutions creates an inclusive and moderate education, which complements each other to form a more tolerant generation, and is ready to face social diversity. The implication of this finding is that the holistic curriculum integration model can be the basis for Islamic education in the future, with recommendations for further research on the challenges of implementation and the role of technology in multicultural teaching in Islamic boarding schools and universities.